Drivers of Wetland Conversion in the Tropical Environment - Oluwafemi Benjamin Adeleke (Center for Journal Management and Publication, 2019)
The study identified factors responsible for wetland dynamics and negative marks produced on the environment in the area.Â It equally suggested efforts aimed at reducing effects of the factors on the environment. The study incorporated both meta-analysis of case studies and questionnaires distribution and administration to the respondents who are mainly members of the Fadama User Group (FUG). The results showed changes in rainfall intensity as the major factor responsible for wetland loss; followed by settlement developments and loss of soil water due to river drainage. The results further revealed the effects of the factors to include siltation of drainages, destruction of ecosystem and loss of wetness, and emergent of heavy flooding. The study concluded by suggesting efforts aimed at reducing the influence of the factors on the environment.